Lewis x Antigen is Associated to Head and Neck Squamous Cell Carcinoma Survival - Rabassa, Martín Enrique (2018)
Head and neck squamous cell carcinoma (HNSCC) is an aggressive disease with poor prognosis without appropriate prognostic markers. Previous research shows that Lewis antigens have been involved in carcinoma dissemination and patients´ survival. Fucosyl and sialyltransferases are the enzymes implicated in the Lewis antigens synthesis. The purpose of this study was to evaluate the prognostic utility of Lewis antigens in HNSCC. We conducted a prospective research including histological samples from 79 patients with primary HNSCC. Lewis x and sialyl Lewis x expression were detected by immunohistochemistry; patient’s data, progression free, and overall survival were documented. A statistical correlation study of antigenic expression and patients´ histopathological variables was performed. Cox regression models with internal validation procedures were employed to analyze survival data. By immunohistochemistry, Lewis x was detected in 34/79 (43%) tumor samples, while sialyl Lewis x only in 11/79 (14%). Lewis x expression showed a positive correlation with tumor differentiation and a better overall survival for Lewis x + patients was detected. Moreover, multivariate Cox’s regression analysis showed that Lewis x is an independent predictor of better overall survival. The in silico analysis supported the presence of deregulated fucosyl (FUT4) and sialyltransferase (ST3GAL4) in the Lewis synthetic pathway related to patient survival. These results suggest that Lewis x expression is associated with a better outcome in patients with HNSCC.